Uma leitura interseccional sobre as relações de poder entre estudantes regulares e pessoas idosas inseridas em disciplinas isoladas de graduação presencial pela Universidade Aberta à Pessoa Idosa da Universidade Federal de Mato Grosso do Sul - Eduardo Ramirez Meza (2022)
This study aimed to analyze, under an intersectional view, the power relations between elderly people and young people (undergraduate students) participating in the extension activity "Elderly Person in Academic Training" of the Institutional Extension Program "Oper University for Elderly Persons” from the Federal University of Mato Grosso do Sul. As a qualitative research, the methodological course included a brief survey of the state of the art, obtaining institutional consent and access to contacts of elderly people and regular students, presentation of an invitation to participate in the research, application of a questionnaire and an interview with the subjects. , tabulation and cross-referencing of sociological profile data and discourse analysis. Due to the Covid-19 pandemic, all contacts with the research subjects were maintained remotely, with the support of distance communication technologies. Participated as research subjects 15 elderly people and 15 young adults, the majority being cisgender women. Among the students, only cisgender men show diversity in terms of sexual orientation. All elderly people are of Christian origin and most are divorced. Elderly people have a higher income than regular students with the same level of education, which can be credited to the “benefits of age”. The intersectional look associated with discourse analysis, illuminated by Foucaultian production, were differentials that marked the research. In the analysis of the speeches, step-by-step statements were found, mainly of a biological nature, for the definition of what it is to be young and what it is to be old, statements that articulate the devices of alliance and sexuality and, among the power relations, the question stood out institutional power, mastery of technologies and respect. The research results offer contributions to (re)think the concepts of youth and old age and the formulations on intergenerationality based on intersectional and power analyses.